711. Rapid, non-invasive detection and monitoring of Bartonella quintana endocarditis by plasma-based next-generation sequencing of microbial cell-free DNA. (31st December 2020) - Solanky, Dipesh; Ahmed, Asim A; Fierer, Joshua; Mehta, Sanjay
Abstract: Background: There are up to 50, 000 new cases of infective endocarditis each year in the United States, of which approximately 20% are culture negative endocarditis (CNE). In-hospital mortality remains high at 20 to 30%. Despite advances in diagnostic testing, determining the timing of surgery and duration of treatment in CNE are significant challenges for clinicians. Plasma next-generation sequencing (NGS) for circulating microbial cell-free DNA (mcfDNA) has shown utility in diagnosing and monitoring the response to treatment in endocarditis. Methods: Serial blood samples were obtained prior to and after aortic valve replacement in a patient with culture negative endocarditis. Microbial cfDNA was extracted from plasma and NGS was performed by Karius, Inc. (Redwood City, California). Human sequences were removed and remaining sequences were aligned to a curated database of over 1, 400 pathogens. Organisms present above a predefined statistical significance threshold were reported and quantified in DNA molecules per microliter (MPM). Chart review was performed for clinical correlation. Results: A 53-year old man with history of homelessness, well-controlled HIV infection and a bioprosthetic aortic valve presented with symptomatic severe aortic stenosis and elevated inflammatory markers 3 years following valve surgery. Transesophageal echocardiography showed a paravalvular leak. Bartonella quintana was detected by Karius NGS (in parallel Bartonella henselae serologies were positive). After 4 weeks of parenteral antibiotics, repeat Karius testing demonstrated a 94% (16-fold) decrease in the Bartonella quintana mcfDNA signal to 8813 MPM. He underwent surgical valve replacement; twenty-four hours after removal of the infected valve repeat Karius testing showed a rapid decay of the Bartonella quintana mcfDNA signal to 103 MPM. The patient completed 3 months of oral antibiotics post-operatively, ultimately returning to his former performance status. Conclusion: Plasma-based next-generation sequencing assays for circulating microbial cell-free DNA offer a unique means of pathogen detection, assessment of infection burden and monitoring of response to both medical treatment and surgical debridement/definitive source control in a case of Bartonella quintana endocarditis. Disclosures: Asim A. Ahmed, MD, Karius (Employee)